The Mishnah in contemporary perspective. - Avery-Peck, Alan J. 1953-; Neusner, Jacob, 1932- (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2006)
This second volume of a two-part project on the Mishnah displays a broad selection of approaches to the study of the Mishnah in the contemporary academy. The work derives from Israel, North America, and Europe and shows the intellectual vitality of scholarship in all three centers of learning. What these articles show in diverse ways is that the Mishnah forms a critical focus of the study of Judaism. The authors of these studies represent the best of contemporary scholarship on the Mishnah. Because of the many viewpoints included here, this is the most representative selection of contemporary Mishnah-study available in any collection in a Western language.